Cryogenic temperature plasticity of a bulk amorphous alloy - Yoon, Kyeu-Sang; Lee, Mirim; Fleury, Eric; Lee, Jae-Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Unlike crystalline alloys, bulk amorphous alloys exhibit a significantly enhanced plastic strain when tested at cryogenic temperatures. It was observed that both the retarded band propagation and the multiple shear banding are the characteristic features of the shear banding behaviors that are responsible for the enhanced plasticity at cryogenic temperatures. This study explores the retarded band propagation behavior at cryogenic temperatures in terms of the increased viscosity of a material inside a propagating band. The formation of multiple shear bands at cryogenic temperatures is also clarified by evaluating the role played by the cryogenic environment in facilitating the creation of disorder, where local deformation nucleates. (C) 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: ATOMIC PACKING DENSITY; METALLIC-GLASS; SHEAR LOCALIZATION; MOLECULAR-DYNAMICS; DEFORMATION; FLOW; BEHAVIOR